Epidermal Growth Factor Receptor Regulates Normal Urothelial Regeneration - Daher, Ahmad; de Boer, Willem I; El-Marjou, Ahmed; van der Kwast, Theodorus; Abbou, Claude C; Thiery, Jean-Paul; Radvanyi, François; Chopin, Dominique K (Laboratory investigation, 2003)
Members of the epidermal growth factor (EGF) family and their receptors are involved in many cellular processes, including proliferation, migration, and differentiation. We have previously reported that these growth factors are expressed and have specific regulatory functions in an organ-like culture model of normal human urothelial cells. Here, we used this model to investigate the involvement of EGF receptor (EGFR) in human urothelial regeneration. Three 4-mm-diameter damaged areas were made in confluent normal human urothelial cell cultures with a biopsy punch. Regeneration was measured, on fixed stained cultures, with an image analyzer, at 4, 24, and 48 hours after injury. Cell proliferation was assessed by 5-bromo-2-deoxyuridine incorporation. To identify EGF family factors potentially involved in the healing process, we studied the effect of these factors on damaged confluent cultures and the level of expression of mRNAs extracted from these cultures. EGFR inhibition of the proliferation and migration of urothelial cells was tested with (1) a specific tyrosine kinase inhibitor (AG1478) and (2) a blocking anti-EGFR antibody (LA22). Exogenously added amphiregulin, EGF, transforming growth factor-α and heparin-binding EGF (HB-EGF) stimulated urothelial regeneration. The damaged areas were repaired by regrowth within 48 hours. Both AG1478 and LA22 inhibited the repair (by 50% and 30%, respectively), as well as proliferation and migration. This regeneration was accompanied by increased HB-EGF mRNA expression in cultures of cells from four of six subjects, but no corresponding change in EGFR protein level was observed. These results indicate that the EGFR signaling pathway is involved in urothelial regeneration. Our data support an autocrine role of HB-EGF in this process and suggest that the EGFR pathway is a potential therapeutic target for modulating urothelial cell proliferation.